COVID-19 and the Rise of Crime in Developing Countries, Using Nigeria as a Case Study - Achudume, Tobi (Research Developments in Arts and Social Studies Vol. 2, 2022)
It is not news that the world came to a halt for about a year, and that we are now operating in a new normal. A substantial amount of research has been conducted on this subject. There has been some disagreement on how the epidemic affected more than simply state economies and the health sector. In many countries of the world, as a result of the virus and the lockdown that followed in the international community, there was a big rise in crime rates and sexual violence in states. This article investigates the rise of crime in Nigeria and how it impacted the country even during a pandemic. This study employs the case study technique to examine the spike in crime and how it occurred during a pandemic.